Research on comprehensive assessment of coastal erosion intensity based on multi index method - Fu, Guowei; He, Mingguang; Chen, Xiaofeng; Fu, Miao; Song, Yanwei; Wei, Chenglong; Wang, Hongbing; Zhang, Daheng (Frontiers in Marine Science, 2024)
The intensity of coastal erosion shows how severe the coast is being scoured and eroded. This study, based on previous research, takes the Qionghai-Wanning coast in the eastern part of Hainan Island as an example. It selects four index factors that influence the intensity of coastal erosion: Annual rate of shoreline change (T1)、Beach annual down-cutting rate (T2)、Beach slope (T3)、 Average particle size of the beach (T4). Utilizing an objective Independent Weight method combined with geographic information technology, the study comprehensively assesses the coastal erosion intensity index of the Qionghai-Wanning coast in the eastern part of Hainan Island. The assessment results classify the study area into six levels: serious erosion (3.45%), strong erosion (6.90%), erosion (20.69%), micro erosion (44.38%), stabilization (20.69%), and accretion (3.45%). Under the overall trend of global climate warming and sea level rise, most sandy coasts are in a state of micro erosion intensity. Strong and serious erosion, on the other hand, are predominantly influenced by human activities and tend to occur in cape-bay, artificial islands, harbors, and other similar locations. Using the Spearman correlation coefficient method to analyze the correlation between various factors and the erosion intensity index, T1 and T2 are the main controlling factors affecting coastal erosion intensity, while the T4 is a secondary factor. Through field surveys of eroded coastlines to validate the assessment outcomes, the accuracy of the multi-index coastal erosion intensity assessment method reaches 82.75%. The assessment method and results can provide a scientific basis for the management, protection, and restoration of coastlines. segment of the coast, This process is primarily evidenced by the retreat of the shoreline, the scouring and down-cutting of the beach surface, as well as the down-cutting of low tidal flats while high tidal flats remain stable, and the coarsening of sediments (Mangor, 2004; Marcel, 2012). In the field of coastal erosion science, research has expanded into various directions as a result of ongoing in-depth exploration. These directions include studying coastal erosion processes and mechanisms (Bruun, 1962;